2019
DOI: 10.3390/ijerph16091573
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Epidemiological Features of Selected Bacterial, Viral, and Parasitic Enteropathogens in Stool Specimens from Children with Acute Diarrhea in Thi-Qar Governorate, Iraq

Abstract: Knowledge of etiology causes of diarrheal illness is essential for development and implementation of public health measures to prevent and control this disease syndrome. There are few published studies examining diarrhea in children aged <5 years in Iraq. This study aims to investigate the occurrences and epidemiology of selected bacterial (Salmonella spp. and Campylobacter spp.), viral (adenovirus, norovirus GI and GII, and astrovirus), and parasitic (Entamoeba spp. and Giardia spp.) agents in stool sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 53 publications
5
40
0
1
Order By: Relevance
“…This result coincided with the result of the researcher, AL-Jeboury [26] in Babylon Governorate, where the highest incidence of intestinal viruses was recorded among children aged (2-3 years). It also coincided with the results of the researcher ,Allayeh et al [27] in Egypt, who found in their results that the highest incidence of viral intestinal infection in relation to (Rota, Astro and Adenovirus) was in the age group of less than one year, as well as consistent with the results of the researcher in Thi Qar, where the highest incidence of injury in the age group was less than two years, which was estimated at (60%) [28].…”
Section: Table (1): Distribution Of Enteric Virus's Infection Betweensupporting
confidence: 89%
“…This result coincided with the result of the researcher, AL-Jeboury [26] in Babylon Governorate, where the highest incidence of intestinal viruses was recorded among children aged (2-3 years). It also coincided with the results of the researcher ,Allayeh et al [27] in Egypt, who found in their results that the highest incidence of viral intestinal infection in relation to (Rota, Astro and Adenovirus) was in the age group of less than one year, as well as consistent with the results of the researcher in Thi Qar, where the highest incidence of injury in the age group was less than two years, which was estimated at (60%) [28].…”
Section: Table (1): Distribution Of Enteric Virus's Infection Betweensupporting
confidence: 89%
“…In Thi-Qar (Iraq), a recent study pointed that Campylobacter spp. (17/155 (10.9%)) were the third most common pathogen to be isolated from diarrhoeal children aged less than 5 years old [10]. Hence, with the objective of developing a quantitative consumer phase risk assessment model for Campylobacter, this study aims to fill the gap in the knowledge regarding the variability in consumer purchase preferences, frequency of consumption of raw chicken meat and cross-contamination practices when handling raw chicken in two settings, Alexandria (Egypt) and Thi-Qar (Iraq).…”
Section: Introductionmentioning
confidence: 99%
“…Among socio-demographic variables, place of residence, education, and age were important predictors associated with occurrence of diarrhoeal illness in the household in the two weeks before the study. In the multivariate analyses (Table 2) water, versus households utilizing reverse osmosis water, in Thi-Qar [37]. A community crosssectional study in Mbour, Senegal by Thiam et al [38] observed children living in better-off families were less likely to have diarrhoea compared to their lower income counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with what was reported from studies conducted in neighboring countries such as Turkey [40], Iran [33] and Jordan [27], where children belonging to mothers with a higher education level (university or diploma) were less likely to have diarrhoea compared to those whose mothers had a lower level education (primary or secondary) or were illiterate. This finding might indicate that those mothers who have a higher education level are attaining more awareness on good child feeding practices, hygiene behaviors and safe handling of water which in turn are important factors for reducing the risks associated with childhood diarrhoea [21,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In addition to mothers' education level, the present study observed that the reported occurrence of diarrhoea is likely to be less in children belonging to mothers aged >25 years compared to mothers aged ≤25 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation